RNA binding protein RBM3 increases β‐catenin signaling to increase stem cell characteristics in colorectal cancer cells. Issue 11 (31st August 2015) - Venugopal, Anand; Subramaniam, Dharmalingam; Balmaceda, Julia; Roy, Badal; Dixon, Dan A.; Umar, Shahid; Weir, Scott J.; Anant, Shrikant
Abstract : Colorectal cancer (CRC) is the second leading cause of cancer deaths in the United States. It arises from loss of intestinal epithelial homeostasis and hyperproliferation of the crypt epithelium. In order to further understand the pathogenesis of CRC it is important to further understand the factors regulating intestinal epithelial proliferation and more specifically, regulation of the intestinal epithelial stem cell compartment. Here, we investigated the role of the RNA binding protein RBM3 in stem cell homeostasis in colorectal cancers. Using a doxycycline (Dox) inducible RBM3 overexpressing cell lines HCT 116 and DLD‐1, we measured changes in side population (SP) cells that have high xenobiotic efflux capacity and increased capacity for self‐renewal. In both cell lines, RBM3 induction showed significant increases in the percentage of side population cells. Additionally, we observed increases in spheroid formation and in cells expressing DCLK1, LGR5 and CD44 Hi . As the Wnt/β‐catenin signaling pathway is important for both physiologic and cancer stem cells, we next investigated the effects of RBM3 overexpression on β‐catenin activity. RBM3 overexpression increased levels of nuclear β‐catenin as well as TCF/LEF transcriptional activity. In addition, there was inactivation of GSK3β leading to decreased β‐catenin phosphorylation. Pharmacologic inhibition of GSK3β using (2′Z, 3′E)‐6‐Bromoindirubin‐3′‐oxime (BIO) also recapitulates the RBM3 induced β‐catenin activity. In conclusion, we see that RNA binding protein RBM3 induces stemness in colorectal cancer cells through a mechanism involving suppression of GSK3β activity thereby enhancing β‐catenin signaling. © 2015 Wiley Periodicals, Inc.